Perubahan Volume Tumor, Jumlah Trombosit dan Kadar D–dimmer pada Karsinoma Payudara Lanjut Lokal Setelah Kemoterapi Neoadjuvan - Fredy Rustomi Damanik; Maman Abdurahman; Kiki Akhmad Rizki (Jurnal llmu Bedah Indonesia, 2014)
Background. Locally advanced breast cancer places approximately 40–60% from all the new cases of breast cancer in developing countries. And this kind of breast cancer requires a combined therapy, i.e. chemotherapy, surgery and radiotherapy. Nowadays, the response of chemotherapy is evaluated from the reduction in tumor volume. There is also another parameter. Since half of patients with breast cancer show abnormalities of routine blood clotting factors, D–dimmer which is a fibrin degeneration product from vascular endothelial growth factor (VEGF) is used. There is an increase of plasma D–dimmer level among 86% of breast cancer patients. There is a strong relationship amongst serum VEGF and platelets count in breast cancer patient. Method. To analyze the correlation, we did an evaluation of the tumor volume, platelets count, and plasma D– dimmer among patients with locally advanced breast cancer, before and after cyclophospamide, doxorubicin, 5–fluorouracil (FAC) combined neoadjuvant chemotherapy. This was a prospective study enrolling 36 subjects. The data is obtained from the history, physical examination, laboratory and or radiological exams as it found in medical record. To have a normal distribution of the subjects, a Shapiro–Wilk test was done. Pearson correlation test was applied in evaluation of the relationship of tumor volume, platelet count and plasma D–dimmer level after chemotherapy. Data was analyzed using the SPSS program ver.19. Results. Tumor volume decreases till 153.811 cm3, the platelet level decreased till 4,958.333/mm3 and the plasma D–dimmer level also decreased up to101.389 ng/ml after FAC regimen. A significant relationship was found in platelet counts and tumor volume after chemotherapy with r of 0,391 (p=0,018). The relationship amongst the change in platelet level and plasma D–dimmer level showed a plateau which is quiet high with the value of r=0,473 (p=0,024). Conclusion. There is a positive correlation of the tumor volume, the platelet level, and plasma D–dimmer level after combined FAC neoadjuvant chemotherapy